Pengaruh Celebrity Endorser, Brand Image, Brand Trust Terhadap Keputusan Pembelian Clear Shampoo Di Kota Denpasar - Wulandari, Ni Made Rahayu; Nurcahya, I Ketut (E-Jurnal Manajemen, 2015)
Basic scientific work is to discuss (1) the effect of celebrity endorser, brand image, brand trust simultaneously influence the purchase decisions Clear shampoo in Denpasar, (2) to determine the influence celebrity endorser, brand image, brand trust partially influence on purchasing decisions Clear shampoo in Denpasar, and (3) to determine the influence celebrity endorser, brand image, brand trust is the dominant influence on purchasing decisions Clear shampoo in Denpasar. The scientific work of Denpasar choose with the help of a data analysis technique multiple linear regression. Through purposive sampling method, a sample of 105 respondents obtained. Data replied with SPSS program proves that celebrity endorser, brand image, brand trust simultaneously positive and significant influence on purchasing decisions Clear shampoo in Denpasar with Fhitung value (144.297)> F table (2.70). celebrity endorser, brand image, brand trust is partially positive and significant impact on purchasing decisions Clear shampoo in Denpasar. Brand image dominant influence on purchasing decisions Clear shampoo in Denpasar
Keywords: celebrity endorser; brand image; brand trust; keputusan pembelian